2011
DOI: 10.1002/mc.20732
|View full text |Cite
|
Sign up to set email alerts
|

Association of cyclin D1 gene polymorphisms with risk of esophageal squamous cell carcinoma in Kashmir Valley—A high risk area

Abstract: Investigation of potential association of SNPs (G870A, rs9344; G1722C, rs678653) of cyclin D1 gene (CCND1) with susceptibility to esophageal squamous cell carcinoma (ESCC) in Kashmir valley (India). The study included 302 subjects comprising 151 ESCC cases and 151 controls. PCR-RFLP and direct sequencing were employed for genotyping. The G870A polymorphism, the individuals carrying GA + AA genotype was having 2.80-fold increased risk for development of ESCC (OR 2.8, 95% CI = 1.77-4.4; P = 0.0001) compared to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
(73 reference statements)
0
23
1
Order By: Relevance
“…If more than 1 geographical or ethnic group was included in the same study, then data from different populations were extracted. Therefore, 8 studies, including 9 populations (Yu et al, 2003;Zhang et al, 2003;Casson et al, 2005;Geddert et al, 2005;Jain et al, 2007;Akbari et al, 2009;Liu et al, 2010;Hussain et al, 2011) with 1898 patients with esophageal cancer and 3046 controls were finally identified: 4 populations were from East Asia [2 Chinese (Yu et al, 2003;Zhang et al, 2003) and 2 from India (Jain et al, 2007;Hussain et al, 2011)], 2 were from West Asia (Akbari et al, 2009), and 3 included Caucasians (Casson et al, 2005;Geddert et al, 2005;Liu et al, 2010). A flow diagram schematizing the process of selected and excluded articles with specific reasons for each is presented in Figure 1.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…If more than 1 geographical or ethnic group was included in the same study, then data from different populations were extracted. Therefore, 8 studies, including 9 populations (Yu et al, 2003;Zhang et al, 2003;Casson et al, 2005;Geddert et al, 2005;Jain et al, 2007;Akbari et al, 2009;Liu et al, 2010;Hussain et al, 2011) with 1898 patients with esophageal cancer and 3046 controls were finally identified: 4 populations were from East Asia [2 Chinese (Yu et al, 2003;Zhang et al, 2003) and 2 from India (Jain et al, 2007;Hussain et al, 2011)], 2 were from West Asia (Akbari et al, 2009), and 3 included Caucasians (Casson et al, 2005;Geddert et al, 2005;Liu et al, 2010). A flow diagram schematizing the process of selected and excluded articles with specific reasons for each is presented in Figure 1.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…A flow diagram schematizing the process of selected and excluded articles with specific reasons for each is presented in Figure 1. With regard to the study design, 3 of these studies were population based (Yu et al, 2003;Zhang et al, 2003;Akbari et al, 2009), and 5 employed a hospital-based design (Casson et al, 2005;Geddert et al, 2005;Jain et al, 2007;Liu et al, 2010;Hussain et al, 2011 …”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…An age-standardized incidence rate of 4.52 per 100,000 of population has been reported for this disease. Recent times have observed a remarkable progress in terms of the pace with which molecular studies including the polymorphic and mutational analysis have been carried on different GIT cancers in the valley that has given an insight about the predominance of variants present in our unique ethnic race (Hussain et al, 2011;Javid et al, 2011;Malik et al, 2011a;2011b;2011c;Rasool et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Casson et al (15), Jain et al (17) and Hussain et al (19) showed a significant association between this polymorphism and esophageal cancer. However, four other studies demonstrated no significant association between this polymorphism and esophageal cancer (13,14,16,18).…”
Section: Resultsmentioning
confidence: 95%
“…The full text of these articles was reviewed intensively and three articles without the control group were excluded. Thus, seven case-control studies (1,154 esophageal cancer cases and 1,678 controls) on the association between CCND1 G870 polymorphism and esophageal cancer risk were included in this meta-analysis (13)(14)(15)(16)(17)(18)(19). Of these included articles, four studies were on Caucasians (15,16,18,19) and three studies were on Asians (13,14,17).…”
Section: Resultsmentioning
confidence: 99%